K-feldspar pIRIR150 dating of the Late Pleistocene sediments in the NW Khangai Mountains (Mongolia) using a standardized dose-response curve approach - Li, Yan; Tsukamoto, Sumiko; Klinge, Michael; Sauer, Daniela; Frechen, Manfred (Frontiers in Earth Science, 2023)
K-feldspar luminescence dating has been widely applied to constrain the timing of Quaternary sedimentation in different environments. However, the measurements are time consuming. Meanwhile, anomalous fading and partial bleaching are the two potential problems inducing dating uncertainty. In this study, sand-size K-feldspar grains extracted from 32 luminescence samples from the northern slope of the Khangai Mountains, Mongolia, were dated using the post-infrared (IR) infrared stimulated luminescence protocol (pIRIR150. Subscript shows the second stimulation temperature). The standardised dose response curves (sDRC) for luminescence dating, which could improve efficiency of measurement, were constructed. The K-feldspar luminescence chronology has been established after careful investigations of fading correction and bleaching degree of the signals. The sDRCs and individual DRC yield consistent ages, indicating that the sDRCs are appliable for luminescence dating with improvement of measurement efficiency. The fading corrected ages using the two fading correction models are generally in agreement. Based on age comparisons between the radiocarbon dates, the fading corrected pIRIR150 and IR50 ages, the pIRIR150 signal was not fully bleached for several samples, while some of the IR50 ages were overestimated due to fading over-correction. The investigated profiles have documented the sedimentary information since the last deglaciation.